Improving Student’s Reading Comprehension by Using Bookr Class Application in Smp Muhammadiyah Jayapura - Irfun, Irfun (Lembaga Riset Ilmiah, 2025)
The objective of this study is to find out whether there is a significant difference in reading comprehension between students who are taught by BOOKR CLASS APP and without using it. CIRC BOOKR CLASS APP was compared with conventional method in teaching-learning process. This study is a quasi-experimental design (Creswell 2012). Purposive sampling is the sample method used in this investigation. Ninety students in the seventh grade at SMP Muhammadiyah Jayapura served as the study's subjects. There two classes were created out of this study. Class A was the experimental group, whereas Class B served as the control group. The pre-test was administered to both classes (experimental and control) prior to treatment. During the study, students in the experimental class were taught using the BOOKR CLASS APP, while the control class was taught using traditional methods. The teaching-learning process lasted five weeks. After the experiment, both classes were given a post-test. The data was analyzed using IBM SPSS Statistics V.30 (Independent Samples-Test). The findings demonstrated a substantial difference between the BOOKR CLASS APP and conventional methods for boosting students' reading comprehension. The experimental class has proven to be more effective than the conventional method.